POTENTIAL ROLE OF L – ARGININE IN SESAME SEEDS FOR DENTAL CARIES PREVENTION - Sari, Rini Puspita; Sari, Morita; Faizah, Ariyani; Cahyani (Journal of Health and Dental Sciences, 2025)
Dental caries is a chronic disease caused by damage to tooth enamel. The epidemiology of the prevalence of dental caries in Indonesia is 88.80%. Some cases are detected in more severe conditions that involve pulp damage. L-arginine is one of the substances that can prevent and inhibit the progression of dental caries pathogenesis. However, few studies have discussed the role of L-arginine. This literature review aims to evaluate the potential role of L-arginine in preventing dental caries. The research uses a systematic review approach on various databases, namely PubMed, Scopus and Web of Science published in the range of 2021 – 2025. Results: After the selection, as well as the screening of articles, 5 RCT articles were found, and 4 review articles were found in accordance with the research objectives. Most studies had observational analysis outputs less 1 year so they did not show long-term results, as well as side effects of L-arginine use. L-arginine can inhibit the progression of pathogenesis of dental caries disease, as well as reduce sensitivity symptoms in the oral cavity. DOI : 10.54052/jhds.v5n2.p151-162